Caracterización de Propiedades Fı́sicas de Promastigotes y Amastigotes de Leishmania braziliensis en Cultivos in vitro Usando Ondas Acústicas Estacionarias y Microfluı́dica (2019)
In this work acoustic standing waves were used in the ultrasonic range to manipulated Leishmania parasites. The aim of this manipulation was to identify changes in the physical properties of promastigotes and amastigotes, which can be related to the cytoskeleton alterations caused by genetic modifications or by parasite adaptation to different enviroments. 3D theoretical model was developed with a dynamical analysis to identify these changes in the parasites physical properties using the acoustic radiation force intensity determinated for Leishmania. It was found that the force magnitude is greater in promastigotes than amastigotes, effect that can be related with simultaneous changes in the parasite volume, density and elasticity by its adaptation to the extracellular enviroments that affect the cytoskeleton. However, differences in the magnitude of the Fpr are associated with the volume when transfected Leishmania parasites, at the same stage, are compared. These results were obtained by measuring, first, the acoustic energy in the devices, where their values were defined between 7 and 9 J /m3 , and, second, and ,second, were determed physical properties of Leishmania such as its shape, by means of particle counter Coulter Beckman Z2 and microscopy images, density, measured with Percoll gradients, and elasticity, extracted indirectly from the 3D model. The physical properties were introduced in numerical simulation for establish Fpr magnitude in Leishmania. In addition, was found that the parasites have an acoustic contrast factor, positive, φ > 0, because these cells move towards the pressure node during acoustic field application. Region where the promastigotes arrive first than the amastigotes to form aggregates that rotate with respect to the node.